THE EFFECT OF PICTURED CARD USED IN JIGSAW COOPERATIVE LEARNING PROCESS TO IMPROVE STUDENT`S CRITICAL THINKING SKILL - M.Robidinsyah M.Robidinsyah; Pramudiyanti Pramudiyanti; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Based on observation and interview of Biology teacher of Al-Kautsar  Senior High School students critical thinking skill were not optimally developed yet.  This experiment aims to find out the influence of applying pictured card media combined with Jigsaw  cooperative learning modeltowards improvement of students critical thinking skill. This study is quasi experiment using pretest posttest group non- equivalent design. Sample were students from X7 and X6  class which obtained from population by  random  sampling technique. Quantitative data was obtained  from the average of pretest and posttest scores and was statistically analyzed using t-test  in 95% confidence levels. Qualitative data were  student’s learning activities and students responses and was  analyzed descriptively. Result of this study shows that the average of student`s critical thinking skill and student learning activities percentage in all observed aspects  improve significantly. The students also gives good responses toward applying pictured card media through cooperative learning model type Jigsaw. Keywords:  picture card media,, cooperative learning of Jigsaw type                     critical thinking skill, protista